2014
DOI: 10.11646/phytotaxa.176.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A re-assessment of Elsinoaceae (Myriangiales, Dothideomycetes)

Abstract: The family Elsinoaceae is a relatively poorly known, but important family within Myriangiales, Dothideomycetes. The genera of this family are mostly plant pathogens and causes disease, such as apple and grape scab. In this paper we revisit the family by examining generic types and analysis of molecular sequence data available in GenBank. Elsinoaceae and Myriangeaceae are morphologically and phylogenetically well-supported families in Myriangiales. In Elsinoaceae, 3 to 10 asci form in locules in light coloured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
20
0
2
Order By: Relevance
“…We treat Brefeldiellaceae as a synonym of Trichopeltinaceae. The family differs from Stephanothecaceae which has individual thyriothecia with hypostromata (Jayawardena et al 2014). Stephanothecaceae may need resurrecting to accommodate Stephanatheca and similar genera, as its fruiting structures are quite unusual in Dothideomycetes (Hyde et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We treat Brefeldiellaceae as a synonym of Trichopeltinaceae. The family differs from Stephanothecaceae which has individual thyriothecia with hypostromata (Jayawardena et al 2014). Stephanothecaceae may need resurrecting to accommodate Stephanatheca and similar genera, as its fruiting structures are quite unusual in Dothideomycetes (Hyde et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hyde et al (2013) placed Pycnoderma in Brefeldiellaceae and also placed the genus in Cookellaceae in the same publication; we agree to it being placed in Cookellaceae based on its thyriothecia clustered together with surface rough, pigmented. Pycnoderma is similar to Saccardinula based on its muriform ascospores, but the thallus is less well-developed than in Saccardinula (Jayawardena et al 2014, Spegazzini 1885, while thyriothecia of Pycnoderma cluster together, with globose asci. Pycnoderma is also similar to Elsinoaceae species based on globose asci, but Elsinoaceae species have wart-like ascostromata, or are small, white to pale yellow or brown, soft, and multi-loculate (Hyde et al 2013).…”
Section: Genera Included Inmentioning
confidence: 96%
See 2 more Smart Citations
“…The asci formed in Schenckiella are rarely observed in the Dothideomycetes. Different dothideomycetes like Elsinoe fawcettii (Jayawardena et al 2014), Polychaeton citri and Pseudocercospora angolensi (Schoch et al 2009) have been reported to cause scab and anthracnose on various Citrus spp.…”
Section: Introductionmentioning
confidence: 99%